Environmental, social and governance (ESG) disclosure and its effect on firm's performance / Fatin Adilah Razali - Razali, Fatin Adilah (2015)
Environmental, social and governance (ESG) is another branch of corporate social responsibility, which have gained more attention from corporate businesses and investors. The new emerging socially responsible investment requires the inclusion of ESG in the companies' business conduct. The ESG information disclosure practices might differ across the country's location. Specific regulation in disclosing the required information is necessary to ensure the information provided will satisfy all stakeholders especially socially responsible investors. The purpose of this study is to examine and compare the level of ESG disclosure between two countries under different ESG disclosure practice requirement. Moreover, this study also examines the element being prioritize or emphasis under ESG disclosure. In addition, the relationship between ESG disclosure and firm's performance measured by economic value added (EVA) is also included in this study. This study is a quantitative study and it employs top 100 companies each listed in Malaysia and Denmark stock exchanges. Using a content analysis method on the companies report in 2013 and comparative analysis (Mann-Whitney U test and Kruskal-Wallis test), the study found that there is a significant different in ESG disclosure and its elements emphasis in both countries. Country regulatory background, norms and believe may effect and influence the level of ESG disclosures and its emphasis. The correlation analysis is employ to test the relationship between ESG disclosures and firms EVA. The result found that there is no relationship exists between ESG disclosure and firms EVA. However, this study considers one-year lag between ESG disclosures in 2013 with firms performance in 2014.This indicates that the information disclosed today may not dictate any changes and improvements in the firms' performance in the following year. Information provided should have significant value to the company and their investors as ethical business conduct facilitate the company's longevity in the market.